Awareness regarding emergency contraception among married women attending urban health centre, Berhampur, Odisha, India - Nayak, Ranjeeta; Panda, Manasi; Padhy, Sarmistha; Mishra, Kumar Guru (International Journal of Research in Medical Sciences, 2020)
Background: In India unplanned pregnancy and illegal abortions still remains a problem. Unintended early pregnancy and frequent childbearing contribute to high pregnancy related morbidity and mortality which can be prevented by use of suitable contraceptives. In circumstances where women are unable to exercise sexual and reproductive decision making, introduction of emergency contraceptive pills may provide important back up option to enable women to control their fertility. Methods: A cross-sectional study was conducted between August- October 2016 among 215 married women of reproductive age group attending the Urban Health Center, Berhampur, to study the awareness about most common methods of contraception, decision-making regarding contraceptive and knowledge and practice of emergency contraceptive pills. Results: This study concludes that most commonly used method was Oral contraceptive pills (28.3%) and major source of information regarding different methods of contraception were through friends and relatives (44.6%). Awareness about emergency contraception mostly came through television. Of those aware of ECPs (14.4%) only 16.1% had used it in their lifetime. Conclusions: Although there is awareness about contraceptives methods, knowledge and practice of emergency contraception is low.